2011
DOI: 10.1111/j.1553-2712.2010.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Gender in Emergency Medicine Research

Abstract: Background: Emergency physicians as front-line clinical specialists can directly advance patient care by understanding how gender-specific approaches may affect evaluation and management of diseases in the acute setting. Yet, it is unclear whether the role of gender is systematically examined in research focusing on emergency care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…the Neurological Emergencies Treatment Trial Network) already exist; however, the science of gender medicine remains largely unexplored in emergency care. 24,25 …”
Section: Evolution Of Gender Medicine As a New Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…the Neurological Emergencies Treatment Trial Network) already exist; however, the science of gender medicine remains largely unexplored in emergency care. 24,25 …”
Section: Evolution Of Gender Medicine As a New Sciencementioning
confidence: 99%
“…The review showed that only 2% of all EM studies reported gender-specific outcomes, and only 10% incorporated gender in their analyses (Figure 1). 25 Twenty-one percent of EM studies did not report the gender of the participants. This manuscript alerted EPs to the absence of reporting of gender-specific outcomes for acute conditions.…”
Section: Evolution Of Gender Medicine As a New Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, confidence in knowledge and self-efficacy in women's health among trainees remains low. 16 Establishing a women's health/SGM curriculum is likely to face the same challenges as other new educational initiatives. We present commonly cited challenges to new educational initiatives and propose strategies to address them.…”
Section: Barriers and Solutions For Implementing A Women's Health/sgmmentioning
confidence: 99%
“…Core EM journals are publishing research studies, educational articles, and commentaries related to sex, gender, and women's health with increasing frequency. 2,15,16 In 2013, the U.S. Department of Health and Human Services Office of Women's Health published findings of a national expert panel summarizing the women's health literature and highlighting opportunities to improve education. The report includes recommendations for curriculum development and calls for the establishment of additional women's health clerkships and fellowships.…”
Section: The Rationale: Why Em? Why Now?mentioning
confidence: 99%